The Twin Dilemma: Successfully Operating a Scholar-Led Journal to Enable Discourse and Empower Researcher Development - Johnson, Gareth (Septentrio Conference Series, 2020)
See RECORDING (starts at 00:53:37). The presentation will explore the configuration of a long-running and successful scholar-led, diamond open-access, interdisciplinary journal Exchanges, published by the University of Warwick, which combines knowledge dissemination with contributor developmental goals. Drawing on experiential data, the presentation provides ethnographic insights into the mutually beneficial outcomes derived from recruiting post-graduate researcher ‘associate editors’ to work on the title. It also problematises the balance between potentially exploitative, collaborative editorial production within the context of necessary academic immaterial labour required to operate an interdisciplinary scholar-led title.